2018
DOI: 10.1177/0038040718822573
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Squeeze: The Struggle of Children to Positively Selected Immigrants

Abstract: Why is it that children of immigrants often outdo their ethnic majority peers in educational aspirations yet struggle to keep pace with their achievements? This article advances the explanation that many immigrant communities, while positively selected on education, still have moderate absolute levels of schooling. Therefore, parents' education may imbue children with high expectations but not always the means to fulfill them. Swedish data on children of immigrants from over 100 countries of origin support thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 104 publications
(171 reference statements)
4
52
1
3
Order By: Relevance
“…Contrarily, we found that immigrants' selectivity does not affect the risk of their child of being retained in secondary education, which is usually the outcome of not meeting basic levels of scholastic achievement. Putting together this finding with the previous one, we can speculate that immigrants' selectivity seems to work more by boosting educational aspirations, and thereby affecting educational decisions, than by improving children's academic performance, a result that echoes those found by Engzell (2019).…”
Section: The Educational Outcomes Of Immigrants' Childrensupporting
confidence: 76%
See 3 more Smart Citations
“…Contrarily, we found that immigrants' selectivity does not affect the risk of their child of being retained in secondary education, which is usually the outcome of not meeting basic levels of scholastic achievement. Putting together this finding with the previous one, we can speculate that immigrants' selectivity seems to work more by boosting educational aspirations, and thereby affecting educational decisions, than by improving children's academic performance, a result that echoes those found by Engzell (2019).…”
Section: The Educational Outcomes Of Immigrants' Childrensupporting
confidence: 76%
“…First, previous studies on the association between immigrants' selectivity and labour market outcomes have measured selectivity as a group characteristic and often through proxies (e.g., Cohen & Kogan, 2006;van Tubergen, Maas, & Flap, 2004). Studies measuring immigrants' selectivity as an individual characteristic investigated its effects on their children's educational outcomes (Engzell, 2019;Ichou, 2014), on their destination country language acquisition (Spörlein & Kristen, 2019), on their self-perception in terms of social position (Engzell & Ichou, 2019), and on their health conditions (Ichou & Wallace, 2019). This paper is, to our knowledge, the first to investigate the association between immigrant selectivity as a direct, individual level measure and labour market outcomes of first-generation immigrants.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A key finding is that ethnic minorities often experience disadvantages in academic performance, yet are advantaged in terms of high educational aspirations and choice of educational path net of previous achievements (Jonsson and Rudolphi 2011;Heath and Brinbaum 2014;Alba and Foner 2015;Kalter and Heath 2018). While the immigrant disadvantage in performance can be explained by limited parental resources, the explanation as to why children of immigrants have so high ambitions, as well as under what conditions these can be translated into actual attainment, is less obvious (Jackson, Jonsson, and Rudolphi 2011;Lee and Zhou 2015;Engzell 2018). The first research question in this article is whether we can observe an immigrant advantage not just in educational aspirations and expectations, but also in terms of school effort, among children of immigrants in Norway.…”
Section: Introductionmentioning
confidence: 86%